Pengelolaan Arsip Digital Sebagai Sumber Informasi Bagi Remaja Masjid Baitul Halim Menggunakan Google Drive dan Dropbox - Hasan, Muhamad; Purnama, Jajang Jaya; Rahayu, Sri; Mukhayaroh, Anna (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2024)
Archives are records or letters that are useful and have value, so it is important to store them properly. In this modern era, archives can be stored in digital form, namely in the form of images, sound, video, writing and so on. Digital archives can be managed through computer programs and stored on digital data storage media. With this transformation, it is certainly very easy for interested parties, such as institutions/organizations that own archives. With digital archive storage media connected to the internet, these archives can be accessed whenever and wherever they are. Nusa Mandiri University as one of the tertiary institutions in Indonesia which always carries out the tri dharma of higher education collaborates with the community in carrying out one of the tri dharma, namely community service. The civitas of Nusa Mandiri University held community service activities with Baitul Halim Mosque Youth (RBH), which is an organization formed by teenagers in the Tegal Parang area, South Jakarta. The community service this time raised the theme of Digital Archives Management as a Source of Information for Baitul Halim Mosque Youth Using Google Drive and Dropbox.